Digital Influencer and Local Brands: Unleashing the Power of Instagram for Promoting Authenticity and Innovation (Open Society Conference, 2023)
This paper explores the potential of Instagram as a powerful tool for promoting local brands examines the effect of the source credibility dimension, which includes expertise, trustworthiness, and attractiveness, on purchase intention through online engagement as an intervening factor. Local businesses need recognition from around. There needs to be an intermediary to introduce local businesses to fashion consumers. The results show that the dimension of source credibility digital influences Purchase Intention and Online Engagement, and the relationship between Online Engagement as an intervening variable can mediate partially. This study's main findings are implications from source credibility dimensions that can create purchase intention without online engagement., with a specific focus on the influential role of digital influencer in driving authenticity and innovation.